Analisis pendapatan pedagang pulsa dan paket data di Kabupaten Tanjung Jabung Barat (Studi Kasus Kecamatan Tungkal Ilir) - Rino Afrialdo; Zulfanetti Zulfanetti; Etik Umiyati (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This research aims to find out and analyze the socio-economic characteristics of pulse kiosks and data packages and to find out and analyze the effect of capital. Product prices sold several credits, and sales volume on pulse and data package traders in Tungkal Ilir District, Tanjung Jabung Barat Regency. The data used in this study is primary data. The analytical tool used is multiple linear regression. The results showed that the variables of capital, the price of products sold, the number of credit balances, and the volume of sales of data packages had a significant effect on the income variable of pulse traders and data packages. In contrast, partially, the variables of working capital and sales volume of data packages had a considerable effect. In comparison, the price of products sold and the number of credit balances do not significantly affect the income variable of pulse traders and package data in Tungkal Ilir District, Tanjung Jabung Barat Regency. Keywords: Traders, Capital, Volume, Balance